Hyperthermic intrathoracic chemotherapy for the treatment of malignant pleural effusion caused by breast and ovarian cancer: a systematic literature review and pooled analysis - Karampinis, Ioannis; Dionysopoulou, Anna; Galata, Christian; Almstedt, Katrin; Grilli, Maurizio; Hasenburg, Annette; Roessner, Eric D. (Thoracic cancer, 2022)
Objectives Breast and ovarian cancer account for over 30% of malignant pleural effusions (MPEs). Treatment of the metastatic disease requires control of the MPE. Even though primarily symptomatic, the treatment of the MPE can potentially affect the oncological course of the disease. The aim of this review is to analyze the effectiveness of intrathoracic chemotherapy in the treatment of MPE caused by breast and ovarian cancer. Methods A systematic literature research was conducted up until May 2021. Studies published in English on patients undergoing either surgical or interventional intrapleural chemotherapy were included. Results Thirteen studies with a total of 497 patients were included. Analysis was performed on 169 patients with MPE due to breast cancer and eight patients with MPE secondary to ovarian cancer. The pooled success rates of intrathoracic chemotherapy for controlling the MPE were 59.1% and 87.5%, respectively. A survival analysis was not possible with the available data. The overall toxicity of the treatment was low. Conclusions Intrathoracic chemotherapy achieves symptomatic control of the MPE in 59.1% of patients with metastatic breast cancer and 87.5% of patients with metastatic ovarian cancer. This is inferior to other forms of surgical pleurodesis. Data from small case series and studies on intraperitoneal chemotherapy show promising results. However, formal oncological studies on the use of intrathoracic chemotherapy for metastatic breast or ovarian cancer are lacking. Further prospective pilot studies are needed to assess the therapeutic oncological effects of this treatment.